Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 504509072 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 1980-2010" ] } The dataset includes 504509072 records from 19293 constituent datasets: 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 791 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 3 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 4 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 10 records from Analyses of the recent components of sediment core PS1277-1. 3108 records from MEXU/Leguminosae. 107 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 3 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 3 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 20 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 17 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 378 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 9641 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 192 records from Happywhale - Humpback Whale in Arctic Ocean. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 147 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 2 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 157 records from Orthoptera - SMF. 3360 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 26 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 2 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 59 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 184 records from An updated checklist of aquatic plants of Myanmar and Thailand. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 791 records from BioGIS - Bryophytes - HUJ collections. 657 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 21230 records from Herbarium Universitatis Daugavpiliensis. 1011 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 616 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 85 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 2 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 181 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1 records from Megaluropidae *. 18792 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1564 records from Plecoptera. 23657 records from Swan Coastal Plain Survey. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 4 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 73 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 7 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 272 records from Bees in the UVM Zadock Thompson Zoological Collection. 14 records from NZCS Brownsberg Nature Park Monitoring. 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 32001 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 1 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 3 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 222 records from Neogene palynomorpha from site 81-552. 27 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 120 records from BIRDRACE The early birds. 1091 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 958 records from RECORD Orthoptera Data. 14128 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 2 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 5 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 11161 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 9 records from Oberservation of birds at station PS14/143 along 49° West. 1711 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 2560 records from Upper Silesian Museum, Bird Observations. 130 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 183 records from Données naturalistes de Quentin ROME. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 76 records from SEWBReC Springtails and allies (South East Wales). 7 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 1549 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 71835 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 370 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 1307 records from National Museum of Natural Science. 200 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 168 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 13 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 12 records from Collections ichtyologiques et herpétologiques (BOUM). 5502 records from Données naturalistes de Bruno OGER. 6984 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 3 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 13 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1015 records from Migration and foraging ecology of Greater Shearwater (aggregated per 1-degree cell). 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6163 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 336 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 97 records from Happywhale - Humpback Whale in Indian Ocean. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 101 records from Foraminifera species abundances from tow TT011_7-MOC66. 57913 records from Fichier communal des ongulés. 6 records from Sächsische Schweiz (Pfaffenstein). 2 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 755 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 1726 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 25 records from Living Cirripedia. 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 84 records from Roter Berg Werdau (Leubnitz). 2 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 992 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 3341 records from University of Nebraska State Museum Birds Collection. 3361 records from University of California Santa Barbara Invertebrate Zoology Collection. 78 records from Fish occurrence in Kama River basin. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 3 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 116 records from Dinoflagellate cysts of ODP Hole 189-1172D. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 14429 records from Entomology Collection at the Natural History Museum of Utah. 2920 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 1175 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 40 records from makran-chabahar-arthropods. 602 records from NMML Small Cetacean Aerial Survey 1997. 169772 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 55963 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 1901 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 14188 records from Fish specimens of Kagoshima University Museum. 37871 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 10912 records from Arctic Species Trend Index (ASTI) : Marine. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 25939 records from Wolli Creek Preservation Society Bird Survey. 552 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 164 records from MLZ Bird Collection (Arctos). 6 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 1 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 4 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 403 records from NMML Gulf of Alaska marine mammal survey 2003. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 38 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 23 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 1902 records from Midden-Limburg Fish Ponds Survey. 21553 records from Herbarium Senckenbergianum (FR) - Fungi. 1808 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 209 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 3 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 682 records from Geometridae de France métropolitaine. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 1640 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 96 records from Planktic foraminifera counts at CTD station PS55/063. 8 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 3779 records from Leicestershire and Rutland Aculeate Records. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 280304 records from First Bird Atlas. 1 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 1905 records from MMS Marine Mammal Survey, PNW 1989-1990. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 33 records from Ensemble des données Orthoptères. 10210 records from United Kingdom National Whale Stranding Database 1913-2008. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 42 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 9 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 899 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 2715 records from Natura 2000 Vallée de la Seille. 6922 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 5795 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 4 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 7045 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 84 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 659 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 704 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 4 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 76 records from BIRDRACE Nachtigallen. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 32 records from Total foraminifera counts of multinet FCA97C_MSN1345. 1 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 309 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 236 records from Lucanidae. 13 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 25345 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 56 records from Birds Specimens of Akita Prefectural Museum. 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 24350 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 54 records from Whale catches in the Southern Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 6058 records from ERBG AVH data. 5472 records from CABI Africa Invasive and Alien Species data. 30129 records from River Biologists' Database (EPA). 3 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 74006 records from Tiroler Landesmuseum Ferdinandeum. 64 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 371 records from Bannwald Burghauser Forst. 130 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 11 records from New England Aquarium Harbor Porpoise Tracking (aggregated per 1-degree cell). 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 9522 records from SEWBReC Bees, Wasps and Ants (South East Wales). 348 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 51 records from UCSC Elephant Seals (aggregated per 1-degree cell). 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 5 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 8 records from HRC Koa Kai Marine Species Monitoring Vessel Surveys November 2010. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 4 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 1849 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 154 records from Sorensen distance for herbivores. 34 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 88 records from Total foraminifera counts of multinet M33/1_MSN1029. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 15 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 12475 records from University of Guam Insect Collection. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 603 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 240 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 2 records from Hydromedusae observed during night dives in the Gulf Stream. 305 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1305 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 320 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 1896 records from MCP-Aves - Coleção de Aves. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 55 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 561 records from Bird specimens of Saitama Museum of Natural History. 85 records from orthopteracollections-nhmj-ioj. 60 records from Invasive alien species Impatiens glandulifera Royle in the Republic of Karelia. 1 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 761 records from Collections of Bioclass, school #179, Moscow. 159 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 6980 records from BLM CETAP AIR Sightings. 1 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 339 records from Mycology collection, Norwegian Forest and Landscape Institute. 184 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 179 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 20 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 1 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 10 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 196687 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 5 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 21 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 10 records from UWIZM Anoles. 2493 records from Pat Livermore's Fungus Records 1976 - 2000. 1 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 399 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 2451 records from Macrobenthos Chukchi Sea, 1986. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 413 records from Herbarium of the Institute of the problems of Northern development (TMN). 5 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 725 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 1107 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 167 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 116 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 10 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 7732 records from Herbier Louis-Marie (QFA) - Collection de lichens. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 2 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 5 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 1 records from Colecção Entomológica IIA. 15546 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 36 records from DMNS Egg Collection (Arctos). 247 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 36 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 11428 records from Communautés adventices des systèmes cotonniers du nord Cameroun. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8801 records from Odonata records from RSPB Reserves 1970-2009. 12 records from Données supplémentaires Atlas des Mammifères marins. 1 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 132 records from Abundance of radiolaria at station UT99-23-2. 1310022 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 2789 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 372 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 728 records from South American Antarctic Marine Biodiversity Literature. 1056 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 17 records from Thirteen new records of ferns from Brazil. 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 1 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 41 records from Happywhale - Leopard seal in Southern Ocean. 1306 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 8466 records from NE Scotland other invertebrate records 1800-2010. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 4 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 1 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 1784 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 706 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 3 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 210 records from Lebensraum Gesamtschule (Langerwehe). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1763 records from Données des collections d'algues du MNHN. 1862 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 1917 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 502 records from Coléoptères Silphidés du département du Loiret. 57 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 2197 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 2 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 1 records from Hazel Dormouse in Ireland. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 23 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 10472 records from Insects, Outer Hebrides. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 189 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 2 records from Sonerila konkanensis (Melastomataceae), a new species from South Goa, India. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 11 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 59 records from Nannofossil abundance of Hole 73-521A. 873 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 5658 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 3 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 4 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 1723 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 124 records from Kirkliston Range stream monitoring. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 108 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 236 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 1 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 12878 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 594 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 488 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 282 records from Vascular plants occurrences in Dokdo islands, Korea, based on herbarium collections and legacy botanical literature. 3 records from Happywhale - Bryde's whale in South Atlantic Ocean. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 60 records from Total foraminifera counts from M35/1_MSN1065. 1993 records from Marine Turtles. 476 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 81 records from Gabon 2009-10: Pongara, Leatherback Turtles (aggregated per 1-degree cell). 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 125 records from Total foraminifera counts of multinet M21/2_MSN650. 16 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 10 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 3 records from Vermont Orthoptera Records from Historic Dot Maps. 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 2277 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 254 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 5 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 94 records from Marine algal (seaweed) flora of Faial Island, Azores. 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 4 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 2385 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 171 records from données araneologiques de LEENKNEGT Virginie. 1349 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 36 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 32646 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 533 records from UTEP Invertebrates (Arctos). 60 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 386 records from Fish occurrence in Kuban River basin. 59 records from Schulteich Freie Waldorfschule Darmstadt. 1 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 22052 records from CNIN/Abejas de México/Apoidea. 915 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 643 records from Flora útil del Municipio de la Huerta, Jalisco. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 12 records from Art´n Vielfalt im Kinderwald. 40 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 3 records from Invasive Non-Native Species, Outer Hebrides. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 111 records from Naturalis Biodiversity Center (NL) - Crustacea. 1 records from Brown algae specimens of Komatsu City Museum. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 12 records from A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 782 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 483030 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 11 records from Hawksbill turtles in Torres Strait (aggregated per 1-degree cell). 411523 records from DATAVES. 16 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 8260 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1489 records from The Broward College Insect Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1 records from Berea College, Ralph L. Thompson Herbarium. 409 records from Distribution of nanoplankton at trap WR2. 1191 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 386 records from Ecosphère_2017_12_18. 6 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 128746 records from Fermanagh Flora. 26453 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 467 records from Isle of Wight non-native invasive species. 2 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 11 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 504 records from Weber State University Herbarium. 87 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 57 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 368 records from UNCW Aerial Survey 1998-1999. 351 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 19 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 79 records from Diatom abundance of Hole 95-613. 1307 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 33 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 4722 records from Atlas of Bats from Continental Portugal 2013. 5831 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 2 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 23 records from Abundance of benthos infauna at station GIK23042-2. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 68 records from Streuobstwiese. 2976 records from SIM-Fungal records compiled by Joan Montón. 102256 records from Western Australian Museum provider for OZCAM. 352 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 3843 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 428 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1706553 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 169555 records from NRW Regional Data: South East Wales Non-sensitive species. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 709 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 3 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 715 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 1 records from A clarification of B. C. Seeman’s Malagasy species of Colea Meisn. (Bignoniaceae). 1 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldstück am Schullandheim Bad Bederkesa. 12 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 72 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 2 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 10 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 15 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 1545 records from NatureMap Calcrete Survey. 453 records from Benthic foraminifera counts of sediment core PS1852-2. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 12 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 25 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 19 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 158 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 141397 records from University of Minnesota Insect Collection. 248733 records from ARABEL - Arachnologia Belgica. 2299 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 75 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 26 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 36 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 72 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 1 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 23 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 77436 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 17 records from Analyses of the recent components of sediment core PS1011-1. 32834 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 14 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 13500 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 3 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 9 records from MVZ Herp Observations (Arctos). 306 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 145 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 830 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 22728 records from Restauración y conservación de Isla Guadalupe. 12 records from Coleção de Coleoptera da Universidade de Brasília. 2092 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 5 records from Natterjack Toads of Ireland. 98 records from Warnowtal (Rostock). 766 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 87 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 2 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 18 records from Happywhale - Gray Whale in North Pacific Ocean. 48025 records from Suivi Temporel des Rhopalocères de France (STERF). 6 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 11 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2 records from A new species of Plurellidae (Ascidiacea: Phlebobranchia) from Papua New Guinea. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 128 records from Total foraminifera counts of multinet POS247/2_MSN1386. 3 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 23 records from Landwehrbach. 2 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 17 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 9781 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 50 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 5 records from Données de VINCENT Alexis (SAPROX). 342 records from Nannofossil abundance of Hole 78-543. 12 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 7193 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 452 records from Glasgow Museums BRC: Chrysomelidae. 4 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 48 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 23 records from Total foraminifera counts of multinet FCA97C_MSN1339. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 2584 records from USAC Mammals Collection. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 193 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 111 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 2319 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 445 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 12 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 1 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 1530 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 425 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 2 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3320 records from BioGIS - Mammals - SPNI. 9 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 19405 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 445167 records from SEWBReC Birds (South East Wales). 371 records from Lepidoptera of Mordovia State Nature Reserve. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 184 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 44 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 1565 records from MEXU/Flora de Oaxaca. 10127 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 486 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 5547 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 83 records from Heavy minerals of sediment core PL94-64. 101071 records from Amphibiens et Reptiles de France (Enquête 2). 375 records from Dolichopodidae of Portugal - dataset 2009-2018. 1865 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 233 records from Données naturalistes d'Alain BERLY. 14920 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 5 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 606 records from Données opportunistes. 1698 records from Red-throated diver national surveys in Scotland - raw data. 1960 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 368 records from Ring ouzel national sample survey in the UK in 1999. 35 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 2634 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 704 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 948 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 151 records from Total foraminifera counts of multinet M36/6_MSN1196. 13 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 2030 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 5 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 44 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 10030 records from Données Entomologiques A. HORELLOU 1988-2018. 16 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 321 records from Foraminifera abundance of Hole 74-526A. 184 records from Dinoflagellate abundance of Hole 81-555. 1 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 40 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 233 records from Records of Halicarcinus planatus at sub-Antarctic regions. 751 records from Herbier National de Guinée (HNG). 14 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 1311 records from Iowa State University Fishes Collection. 404 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 455 records from EDIT - ATBI in Gemer area (Slovakia). 15780 records from Global compendium of Aedes albopictus occurrence. 1 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 8 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 150 records from AKG-Gelände (Bensheim). 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 23 records from Benthic foraminifera abundance of Hole 93-603. 8895 records from WOLL AVH data. 1389 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 27 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 407 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 143 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1675 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 9419 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 15 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 192 records from Inventaire et regroupement de données Natura 2000. 1788 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 125873 records from Données de la flore d’Alsace (SBA). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 2052 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 121 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 8460 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 26 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 1666 records from Distribution of major planktic foraminifer at Site 177-1090. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 102 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 83555 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 2 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 3402 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 1123 records from SWECO. 826 records from Données naturalistes de Loïc SALAUN. 292 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 674882 records from Flore Franco-Belge. 8525 records from EAC - Herbário Prisco Bezerra. 2507 records from East Ayrshire Species Database. 6194 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 4686 records from Collection Pisces SMF. 178 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 10449 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 720 records from MEXU/Tipos de plantas vasculares. 19 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 242 records from Landschaftspflegehof (Berlin). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 10 records from Bachpatenschaft Beeke. 5895 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 11 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 971 records from Données naturalistes de Daniel PAVON. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 14 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 708 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 59 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 96 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 130108 records from Estonian Nature Observations Database. 8 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 7 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 11 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 2 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 2 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 29730 records from Botanical Museum, Copenhagen, Mycology Herbarium. 4 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 4718 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 9 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 56503 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 106692 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 4 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 3 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from Planktic foraminifera counts of multinet PS2616-5. 16 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 369 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 22212 records from Fife Nature Records Centre combined dataset. 3 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 4 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 15 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 30 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 2818 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 270 records from BIRDRACE Niederlausitz-Team. 2 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 324 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 83 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 961 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 11 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 248 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 10 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 3586 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 4 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4 records from Descriptions of two new shell-dwelling species of Metriaclima (Cichlidae) from Lake Malaŵi, Africa. 23 records from TRAS LA RUTA DE LAS TORTUGAS GOLFINAS EN LOS CABOS, BCS 2009-2018 !! (aggregated per 1-degree cell). 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 36475 records from Données naturalistes de Monsieur François FOURNIER. 1 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 912 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 37679 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 11 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 4 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 343 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6026 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 1358639 records from Hatikka Observation Database. 130 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 45 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 53 records from Données naturalistes de Monsieur JOURDE Rémi. 106541 records from inatura - Erlebnis Naturschau Dornbirn. 168 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 9 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 464 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1459 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 917 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 2 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 6 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 18147 records from WTSWW Data: All Taxa (West Wales). 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 38 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 412291 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 170300 records from South Australian Museum Australia provider for OZCAM. 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 74 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 31 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 3 records from Coccolith counts of multinet M32/5_MSN981. 8 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 15 records from Brock University Herbarium (BU). 160 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 117 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 7115 records from Whicher Scarp Flora Survey. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 2269 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 2 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 57 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 2 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6132 records from Modernisation des ZNIEFF du PnrL. 4 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 2 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 29 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 43 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 11 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 110210 records from Tasmanian Museum and Art Gallery provider for OZCAM. 13 records from TTRS Mammals. 3 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 82 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 730 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 4 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 69476 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 600 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 1495 records from Chrysomelidae beetle data from iRecord. 17 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 9920 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 8 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 43 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 20 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 541 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 12 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 613 records from MHA Herbarium: Collections of mosses from Yana-Indigirka Region, Yakutia, Russia. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 4 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 893 records from La familia Asclepiadaceae en México. 1 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 24 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 370 records from Otter survey of Ireland 2004 & 2005. 1038 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 2128 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 54 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 521 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 44 records from Microzooplankton abundance and biomass at station TT045_15-2. 6101 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 36549 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 11675 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2770 records from Database for alien invasive plants occurrences in Germany. 9 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 6 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1320 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 531 records from 成龍溼地鳥類生態紀錄. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 2 records from Chalinochromis cyanophleps, a new species of cichlid fish (Teleostei: Cichlidae) from Lake Tanganyika. 62 records from Benthic foraminifera abundance of Hole 84-566C. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 115 records from Strathclyde badger sett surveys 1996-2000. 454 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 871 records from SEFSC Southeast Cetacean Aerial Survey 1992. 57465 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 1238 records from OUPR - Herbário "Professor José Badini". 8 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 38611 records from National Biodiversity Data Bank. Observation records, 1900-2014. 303 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 6 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 11659 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 7483 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 1 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 7 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 1108 records from SWFSC Marine Mammal Survey, STAR 2003, Cruise 1623. 54 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 145 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 12 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 3 records from Albury Wodonga Nature Map. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2175 records from Jardín Botánico Atlántico, Gijón: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 9 records from étude entomologique de la ZSC du Bois de Vaires. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 2410 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 587 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 338 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 523 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 106 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 67 records from Fish Fauna of Berlin. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 2079 records from Kherson State University herbarium (KHER), Department of Botany. 29 records from Total foraminifera counts of trap L3_92_45. 432 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 6170 records from Nijmegen Natural History Museum (NL) - Herbarium. 40 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 74 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 1937278 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 3 records from Département_du_Var_2017_12_18. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 106 records from Total foraminifera counts of trap L2_92_A42. 52 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 127 records from Wildlife Observations Bardon Hill 31.5.09. 45 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 1 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 22604 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 5 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 985 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 30 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2038 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 72 records from Eufáusidos norte de Chile. 33419 records from WADFW PSAMP W1993. 5 records from The Unicorn exists! A remarkable new genus and species of Perilissini (Hymenoptera: Ichneumonidae) from South East Asia. 8 records from Hyobanche thinophila (Orobanchaceae), a new species from the Western Cape of South Africa. 24 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 5 records from Annales de la Société entomologique de France [1832- ]. 56 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 200 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 3 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 269 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 65988 records from Finnish Floristic Database (Literature Sources). 9 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 1053 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 1 records from A new species of Nasusina Pearsall from Colorado (Lepidoptera: Geometridae: Eupitheciini). 53073 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1719 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 4 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 744034 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 16 records from Bohemannia auriciliella (Nepticulidae) specimen data. 1365 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 1 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 17 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 1 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 481 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 212 records from Planktic foraminifera abundance of Hole 84-567A. 1 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 1242 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 5858 records from K-State Museum of Entomological and Prairie Arthropod Research. 27286 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 90 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 169414 records from Marine benthic dataset (version 1) commissioned by UKOOA. 214 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 5229 records from European Moth Nights. 5665 records from The Dolphin Project. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 65 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 288 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 73 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 754 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 661 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 84 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 2 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1036 records from BUND - Dassower See (Lübeck/Dassow). 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1136 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 18 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 1033 records from Leif Richardson Vermont Bee Specimens. 3 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 153 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 2330 records from Collection Crustacea - ZMB. 374 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 309 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 14 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 66 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 1 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 2079 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 3 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 17 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2310 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 15 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 26 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 32065 records from The national database for marine data (MADS). 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 248 records from Canary Islands - OAG (aggregated per 1-degree cell). 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 97 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 975 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1230 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 331 records from Pollen data of trap CB4. 20 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 10 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 92 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 3 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 4 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 11 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 49 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 80 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 384 records from "Schwarzwassertal" bei Pobershau. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 23651 records from Plan de vertebrados de la Patagonia. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 2954 records from Distribution of planktic foraminifera of sediment core M35003-4. 10849 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 85557 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 7 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (Mölltal, Kärnten). 858 records from LPO_PACA_2017_12_18. 132 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 11 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 42 records from Targeting a portion of central European spider diversity for permanent preservation. 195 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1828 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 589 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 391 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4105 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 32 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 24 records from Abundance of benthos infauna at station PS1240-1. 1113 records from Marine algal flora of Flores and Corvo Islands, Azores. 1079 records from Mediterranean seabird surveys 99/00/02. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 1 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 27 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 419 records from données arachnologiques de CARR David. 2 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 140 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 2898 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 440 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 119 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 188 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 12354 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 4725 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 4 records from Two new species of Carcinoplax H. Milne Edwards, 1852, and Pycnoplax Castro, 2007, from the western Pacific, and a description of the female of Thyraplax truncata Castro, 2007 (Crustacea, Decapoda, Brachyura, Goneplacidae). 134 records from BIRDRACE Griffin Wood Warblers. 91 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 7 records from Planktic foraminifera abundance of Hole 94-611B. 1403 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 4 records from Two new species of the genus Sinopodisma (Orthoptera: Acridoidea: Catantopidae: Podisminae) from China. 2 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 2 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 203 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 3 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 17 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 197 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 5 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 8 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 2 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 234 records from Pollen analysis of sediment profile BLA00 from Blankensee. 1 records from DRYMONIA MEXICANA (GESNERIACEAE), A NEW ENDEMIC SPECIES FROM VERACRUZ (MEXICO) Laura Clavijo. 7104 records from NCSM Non-molluscan Invertebrates Collection. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 301 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 89255 records from The AAU Herbarium Database. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 173 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 146 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 13 records from North Carolina Rehabilitated Sea Turtle Monitoring Project (aggregated per 1-degree cell). 734 records from Colecção Entomológica do Museu de História Natural de Maputo. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 722 records from Heritage Trees of Ireland. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 354 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 18 records from Craigellachie NNR invertebrate records compiled from SNH files. 240 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 9 records from Hydrographic profiles in South West Atlantic Ocean derived from Southern Elephant seals dives. 270 records from Collection Polychaeta - ZSRO. 6635 records from imr_mareano_rpsledge. 7 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 39370 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 4 records from RISC Non-Native Species Records for Zebra Mussel. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 796 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 59 records from Cayman Islands 2004: Loggerhead & Green Turtles (aggregated per 1-degree cell). 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 10 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 32 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 243 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 18 records from Freshwater fish records via iRecord - additional species. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 20 records from Abundance of benthos infauna at station GIK23055-1. 124 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 2 records from A new species of Anchoviella Fowler, 1911 (Clupeiformes: Engraulidae) from the Amazon basin, Brazil. 6 records from Benthic macrofauna abundance of sediment core 13200-017. 356 records from Ixias butterfly specimens at Museum Zoologi Bogor, Indonesia. 4 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 83 records from Riodinid butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 2051 records from Gunma Museum of Natural History, Fungi Specimen. 45 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 2 records from Kirchenforst. 4867 records from Pteridophyte of the Urals and adjacent areas. 33 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 3 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 248 records from DUML vessel-based line transect surveys for proposed Onslow Bay USWTR site 2007-2010. 8 records from Qarshi Botanical Garden. 1620 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 2 records from Scorpions of the Horn of Africa (Arachnida, Scorpiones). Part XIV. Hottentotta somalicus sp. n. (Buthidae) from Somalia. 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 86633 records from PIROP Northwest Atlantic 1965-1992. 4 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 102 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 25 records from Happywhale - Southern Right Whale in South Atlantic Ocean. 28 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 119 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 134587 records from UWFC Ichthyology Collection. 70 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1331 records from Mycological Collection of Osaka Museum of Natural History. 4041 records from Auburn University Museum of Natural History Invertebrates. 3 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 58 records from Mamíferos laguna El Tinije. 3572 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 3 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 12213 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 352 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 1573 records from Marie-Victorin Herbarium (MT) - Bryophytes. 22 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 12 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 188274 records from National Benthic Inventory. 6 records from Phenological Center - Fishes (Murmansk). 109 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from BIRDRACE Die Wendehälse. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1071 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 183 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 4965 records from Scotland Otter Survey Database. 1018 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 127179 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 660 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 553 records from Ornithological observations in the Kharkiv region of Ukraine. 18782 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 152320 records from Carnet B Lorraine. 1837 records from Naturalis Biodiversity Center (NL) - Pisces. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 387 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 2 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 495 records from Radiolaria assemblage in sediment core GIK23414-6. 308 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 286 records from Myxomycetes collection of the University of Eastern Finland. 1097 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 125806 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 43 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 5 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 1 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 9 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 2 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 786 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 1 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 15 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 110 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 2808 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 1984 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 24036 records from Arizona State University Hasbrouck Insect Collection. 49439 records from CCAMLR historic KRILL. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 2788 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 8 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 5 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 156 records from Chironomid remains in the sediment sequence of Site PG1212. 1299 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 2273 records from Lista florística de la Costa Grande del estado de Guerrero. 6 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 68305 records from MDFRC macroinvertebrate survey. 168 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 62 records from Amtsrain Apolda-Zottelstedt. 72 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 83 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 59703 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 4 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 30 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 310 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 180 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 77 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 10 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 99 records from Dorfrand Mauderode. 122 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 61 records from Shrews of Poland. 4 records from Archaeal 16S Ribosomal RNA RefSeq Targeted Loci Project. 30 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 5 records from Amoeboid protists isolated from ancient Siberian permafrost. 1635 records from Inventaire des Mollusques Sphaeriidae de France. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 14081 records from données aranéologiques de CORNIC Jean-François. 20 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1615 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1313 records from Diatom assamblage in samples from sediment trap OG5. 1374 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 463 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 5 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 2454 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 1 records from Insectos asociados a cultivos de Albahaca y Ají en Santa Marta. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 59879 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 25 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 706 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 9153 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 103225 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 23 records from Ackerrain Plönhagen. 158 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 194 records from Malawi-Histeridae-Biodiversity-Data. 13286 records from Swiss National Diplopoda Databank. 10554 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 242 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 23 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 34 records from Microzooplankton abundance and biomass at station TT043_4-1. 313 records from BIRDRACE Gätkes Erben. 107 records from Distribution of seabirds at sea in the Gulf of Carpentaria, Australia (1990-1991). 1794 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3249 records from Benthos counted on dredged samples during Valdivia cruise VA53. 2 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 10547 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 52 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 19 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 729 records from Carabidae of the European North-East of Russia. 3013 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 6 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 1 records from The genus Chionanthus (Oleaceae) in Cambodia, Laos and Vietnam. 12 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 862 records from Palynological analysis of sediment core GeoB9508-5. 3 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 22 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 30 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2010. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 13667 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 283 records from Flux data of NU2_trap (Table A1). 3927 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2297210 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 22 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 14 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 17 records from Bishop's University Insect Collection (BUIC). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 223165 records from BioFokus. 97 records from Anymals+plants - Citizen Science Data. 830 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 41 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Happywhale - Blue Whale in Southern Ocean. 3818 records from Happywhale - Humpback Whale in North Atlantic Ocean. 1950 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 464 records from CNAN/Scorpiones. 94 records from Total foraminifera counts of multinet M26/1_MSN845. 39 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 4 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 600 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 1 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 5 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 58 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 2 records from Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera. 10 records from Rosa gallica L. in "Medobory" Nature Reserve. 13 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 40 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 2834 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2056 records from Flora vascular acuática de la cuenca del Río Tamesí. 11 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 375 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 451 records from Patterns of abundance and size of dictyoceratid sponges among neighbouring islands in central Torres Strait (CRC-TS Project: Task Number T1.6a) 2005. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 501 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 814 records from flower availability 2008 Hainich. 513 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 8673 records from Andes to Amazon Biodiversity Program. 46 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 8 records from Données naturalistes de Stéphane ORIO. 319 records from Inventario herpetofaunístico del noroeste de Hidalgo. 244 records from WildesMoor bei Schwabstedt. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 17 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 307 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 4 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 17574 records from CUMV Fish Collection. 2083 records from MUST, Insecta. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 23 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 393219 records from Données ONF faune-flore-fonge. 10 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 348 records from Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 2 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 20871 records from University of Tennessee Fungal Herbarium. 1213 records from University of Michigan Museum of Zoology, Division of Mollusks. 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 2103 records from Flora ficológica de la huasteca potosina. 126 records from Range table from benthic foraminifers in ODP Hole 144-874B. 2821 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 56418 records from DASSH Data Archive Centre Academic Surveys. 1293 records from Herbier de Wallis et Futuna. 17 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 298 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 142 records from Indo-Pacific bottlenose dolphin observations in the Clarence River 2003-2006. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 107124 records from University of Florida Invertebrate Paleontology. 73 records from The ant genus Strumigenys Smith, 1860 (Hymenoptera: Formicidae) in western North America North of Mexico. 118681 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 1 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 407 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 43 records from Vogelstimmenführung durch den Tiergarten. 2 records from Studies in Malagasy Eugenia L. (Myrtaceae) - V: Eugenia quadriphylla N. Snow & Callm., an unusual and rare new species from the northeast. 327 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 1260 records from Butterfly_conservation_2017_12_18. 1399 records from Inventaires faune. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 69309 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 8 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 16992 records from Données bibliographiques et opportunistes Odonates issues du SIRF. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 461 records from Benthic foraminifera counts of sediment core GIK23342-6. 502 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 99 records from Düne am Ulvenberg (Darmstadt). 9 records from Synopsis of the parasitoid wasp genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) in Australia, with the description of seven new species. 8490 records from Mammals housed at MHNG, Geneva. 1 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 73 records from Löydös Open Invasive Alien Species Observations. 330 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 10 records from Sediment properties of core PLG95B_01BOXG. 1745 records from Swiss Psyllid (Hemiptera) Collections - Basel. 4 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 257 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 60 records from UWIZM Mantodea. 359 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 28 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 1 records from Taxonomic study of Hoplias microlepis (Günther, 1864), a trans-Andean species of trahiras (Ostariophysi: Characiformes: Erythrinidae). 240 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 115 records from Mollusca specimens of Kuroshio Biological Research Foundation. 204 records from données bibliographiques diverses (non araignées). 6 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil. 7 records from Small, uniform, and rarely collected-an integrated taxonomic revision of Afromicracis bark beetles (Coleoptera, Scolytinae). 276 records from Phenological Center - Plants (Murmansk). 1 records from Four new species of Scaphochlamys (Zingiberaceae) from Peninsular Malaysia. 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 1518 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 2 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 25 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 810 records from Bird specimens of Komatsu City Museum. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 83 records from Total foraminifera counts of multinet M21/5_MSN728. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 7 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 3 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 60 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 10 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 19 records from Collection Crustacea - ZSRO. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Sinaloa_2008). 682 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1554 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 157 records from BIRDRACE Rheinische Wasserrallen. 91 records from Loup 2004 présence régulière communale (réseau Loup-Lynx ONCFS). 22 records from Cetacean sightings off Turkey 2006-2011. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 3 records from Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis. 1144 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 2 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura Diogenidae) from shallow coastal waters in Japan. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 493 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 3 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 18 records from Données coléoptères de l'Association des Entomologistes de Picardie. 1232 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 106 records from Total foraminifera counts from multinet M31/2_MSN890. 2535 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 932 records from CNAN/Araneae. 42 records from Estimated plankton abundance at station PS63/064-6. 17 records from The Smicridea (Smicridea) fasciatella species group (Trichoptera: Hydropsychidae) in Brazil: six new species and new distributional records. 13353 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 7 records from New apinnate Prionospio (Annelida: Spionidae) species from southeastern Brazil. 4 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 487 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 105 records from A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini). 20 records from Taxonomic review of the Hyphessobrycon panamensis species-group (Characiformes: Characidae). 372 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 1265 records from Benthic foraminifera abundance of Hole 84-570. 1074 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 8282 records from University of Nebraska State Museum Fish Collection. 9 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 88 records from Colección de Zoología Invertebrados - Helmintología. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16198 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from Happywhale - Crabeater Seal in Southern Ocean. 11 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1 records from Collection ornithologique A. Maës. 401 records from Planktic foraminifera distribution of sediment core SU81-07. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 28 records from Mammal specimens of Komatsu City Museum. 33 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 41 records from Örtzemündung (Stedden). 19195 records from National Stag Beetle Surveys (Great Stag Hunts). 1734 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 258 records from Données du naturaliste Arnaud Bak. 59198 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 11318 records from JCT AVH data. 11300 records from University of Tennessee Bryophyte Herbarium. 1146 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 1 records from A new species of the Goblin Spider genus Predatoroonops Brescovit, Rheims & Ott 2012 (Araneae, Dysderoidea: Oonopidae), with new records for the genus. 1871 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 6540 records from Likona Invertebrates. 73 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 22 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 127823 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 338 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 6 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 575 records from Nannofossil abundance of Hole 75-530A. 2 records from Happywhale - Fin Whale in South Atlantic Ocean. 102 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 4853 records from DBRC Hemiptera species records 1969 to 2015. 38 records from BB-Biodiversität a. 1 records from Collection Myriapoda - SNSD. 945 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 66792 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 2630 records from Dorset SW Pilot species dataset. 43 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 96 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 154 records from Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 381 records from MCCC - Mendocino College Coast Center Herbarium. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 7928 records from Cumbria Non Native Invasive Species. 459 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 2518 records from Vegetation of Rybachy Peninsula and Srendny Peninsula, Murmansk Oblast, Russia. 176 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 1667 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 982 records from Diatom assamblage in samples from sediment trap OG4. 272 records from DAR AVH data. 132493 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 15 records from Review of the Orphninae (Coleoptera: Scarabaeidae) of Sri Lanka, with description of a new species of genus Orphnus Macleay, 1819. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 33 records from DBL_Life. 533 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 555 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 1128 records from Océanopolis mammifères marins en Bretagne 1993-2015. 5 records from Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae). Part 19. New species from Indonesia and Malaysia. 18310 records from BLS Rare and Threatened Lichen Records: England. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 346 records from Abundance of phytoplankton in the Marmara Sea collected during the Bilim 2 cruise in Oktober 2008. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 19535 records from Eden Arthropod Azores Database. 78 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 5 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 1911 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 765 records from Abundance and distribution of coastal, inshore zooplankton in the Huon Estuary and D'Entrecasteaux Channel, Tasmania, Australia (2004-2005). 92 records from BID-Malawi-Arctiidae-Biodiversity-Data. 893 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 1345 records from Weevils of Poland. 4 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1730 records from Arachnida of Costa Rica (INBio). 8 records from New and confirmed records of fruit flies (Diptera, Tephritidae) from Italy. 23 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 1966 records from Ross A. Layberry, Collection. 30 records from Occurrence of some antimalarial plants from Cameroon. 9 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 22 records from Early Land Plants Today: Index of Liverworts & Hornworts 2013 - 2014. 2160 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 64 records from Planktic foraminifera assemblage in sediment core SU90-I06. 50 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 79 records from Total foraminifera counts of multinet POS247/2_MSN1384. 18071 records from Fishes of INEP and NFH collections. 82704 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 5 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 44 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 75 records from Naturpark Kottenforst-Ville 19.6.09. 2 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 224 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 788 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 19277 records from Marine Water Column Samples Targeted loci environmental. 73 records from Swedish Malaise Trap Project (SMTP) - small Sciaroidea families. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 1 records from A new pygmy species of box jellyfish (Cubozoa: Chirodropida) from sub-tropical Australia. 51 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 47 records from Sea lamprey distribution and abundance in the River Spey: phases II and III, 2001/2002. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 392 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 13 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 136 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 256 records from The Golden wasps collection (Chrysididae) at the Staatliches Museum für Naturkunde Stuttgart. 316 records from MUFAL herbarium - Museu de História Natural da Universidade Federal de Alagoas - Herbário Virtual REFLORA. 4020 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 68 records from Montana State University Billings. 207 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 333 records from renaturierter Main (Kemmern bei Bamberg). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 479 records from Geochemistry and sedimentology on core POS200/10_28-1. 413 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 19280 records from Observations Regelink Ecology and Landscape. 41163 records from Oskarshamn herbarium (OHN). 10034 records from Museu Paraense Emílio Goeldi - Diptera Collection. 704 records from NEFSC Aerial Survey - Summer 1998. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 1143 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 1 records from A new Occidozyga from Sarawak, Malaysian Borneo (Anura: Dicroglossidae). 768 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 53 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 19250 records from Herbarium Senckenbergianum (FR). 4469 records from Invertebrate Zoology Division, Yale Peabody Museum. 2 records from DREAL Auvergne - Reptiles - 2015. 12 records from Six new species of Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) with redescription of additional species and new distributional records. 399 records from Merseyside BioBank Active Naturalists (unverified). 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 31 records from New Species And New Records Of Plecoptera From Korea And The Russian Far East. 119 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 229 records from Sea trout entering the rivers Adour and Nivelle in south-west France at the start of the 21st century. 327 records from Ectomycorrhiza species on all VIP´s April 2008. 4 records from Nymphs of some Nearctic leafhoppers (Homoptera, Cicadellidae) with description of a new tribe. 57966 records from CHSC - CSU Chico, Chico State Herbarium - Vascular Plants. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 33482 records from Swiss National Vespoidea Databank. 7 records from CHAS Ichthyology Collection (Arctos). 45 records from Planktic foraminifera abundance of Hole 73-520. 17 records from Nachtinsekten am Muldenufer. 621 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Ernst Krenkel" in 1992”. 1517 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 424678 records from Israel Nature and Parks Authority. 55 records from Range table from benthic foraminifers in ODP Hole 171-1052A. 10 records from New Species And Records Of Asian Peltoperlidae (Insecta: Plecoptera). 19 records from Colección de muestras biológicas del Centro Oceanográfico de Canarias. 10 records from NMML Harbor Porpoise Aerial Survey, Bristol Bay, Replicate 2, 1991. 6392 records from Micro-moths distribution for Dumfries and Galloway. 27 records from Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae) from the southern South American Transition Zone and boundaries: taxonomic overview with four new species. 1298 records from Données araignées de JACQUET Claire. 1191 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 555 records from NEFSC Aerial Survey - Experimental 2002. 194 records from Pottundkopp. 84 records from Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 1 records from New species of Crella (Pytheas) Topsent, 1890 and Crellomima Rezvoi, 1925 (Crellidae, Poecilosclerida, Demospongiae) from Chilean shallow and Argentinean deep waters, with a synthesis on the known phylogenetic relationships of crellid sponges. 5652 records from Catálogo de insectos de la colección del Centro de Entomología. 1169 records from Colección de Mamíferos (Mammalia) del Museo de Historia Natural de la Universidad de Caldas, Colombia. 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 1160 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 3 records from Two new species of eyeless amphipods from a coastal area in Japan (Crustacea: Amphipoda: Hadziidae, Melitidae), with reinstatement of the genus Paraniphargus Tattersall, 1925. 1 records from Emeia gen. nov., a new genus of Luciolinae fireflies from China (Coleoptera: Lampyridae) with an unusual trilobite-like larva, and a redescription of the genus Curtos Motschulsky. 72 records from (Table 3) Occurrence of dinoflagellate cyst species in ODP Hole 113-696B. 19 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 386 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (2), 2008 - Données faune. 2970 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 4 records from Gastrointestinal nematodes of Paramelomys levipes and P. mollis (Rodentia Muridae) from Papua, Indonesia and Papua New Guinea with the descriptions of three new genera and nine new species (Nematoda). 40 records from DAYO: Invasive Alien Reptiles in the Philippines. 2 records from Two new species of Styela (Tunicata: Ascidiacea) from the tropical West Atlantic Ocean. 91 records from New state records for Coniopterygidae (Neuroptera) with an updated list of species in North America north of Mexico. 242 records from MPM Herpetology. 26 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 4 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 2072 records from Aves del Distrito de Páramos en los departamentos de Nariño-Putumayo. 36498 records from Fairchild Tropical Botanic Garden (FTG). 10 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 1454 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 103 records from Antarctic Jellyfish. 18 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 24 records from Données naturalistes d'Audrey SAVOURE-SOUBELET. 1 records from A new species of the genus Mallomonas (Synurophyceae), Mallomonas spinosa sp. nov., from Vietnam. 364368 records from National Trust Species Records. 121879 records from Australian National Wildlife Collection provider for OZCAM. 422 records from Diversité floristique des espèces menacées prioritaires du Bénin (Afrique de l'Ouest).. 17112 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Collembola). 1659 records from HUSC - Herbário Unisanta. 5885 records from Crispin S. Guppy Collection. 132 records from Copepoda associated with Caribbean reef-dwelling cnidarians, echinoderms and sponges. 63 records from Données naturalistes d'Emmanuel ICARDO. 942 records from NHM, Heteroptera. 688 records from Algae, Norwegian College of Fishery Science. 55 records from USWTR JAX Aerial Survey -Left side- 2010-2011. 2 records from Alloscorpiops citadelle sp. n. from Thailand (Scorpiones: Euscorpiidae: Scorpiopinae). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1372. 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 1 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 636195 records from Australian Museum provider for OZCAM. 116 records from Revision of the South African endemic bee genus Redivivoides Michener, 1981 (Hymenoptera: Apoidea: Melittidae). 1 records from 5. Wiener Gemeindebezirk. 5596638 records from Observation.org, Nature data from around the World. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 58 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 3 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 3 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 74 records from pbzt_insect_biodiversity. 1 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 217 records from NZCS Upper Tapanahony Expedition 1991. 148 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 804 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 3 records from DD_cyano Targeted loci environmental. 5 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 53 records from Coleção de Nematoda do Museu Nacional - UFRJ. 1 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 5661 records from Inventory of plant species through Benin (West Africa). 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 69 records from Total foraminifera counts of multinet M21/5_MSN731. 14 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 2 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 966 records from Planktic foraminifera abundance of Hole 72-516F. 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 21 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 504 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 2011 records from UNCW Right Whale Aerial Surveys 2008. 4 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 6 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 1 records from A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria. 1997 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 2612 records from Fungi specimens of Saitama Museum of Natural History. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 4 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 6 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 19 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 631 records from Planktic foraminifera abundance of Hole 72-518. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 262 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 605 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 208 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 325 records from Bosque Mesófilo de Montaña de México. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 63 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 13182 records from Inventaire des Ephémères de métropole (Opie). 308 records from Echinodermata of Montenegro (South Adriatic). 255 records from Tetrápodos de Uruguay. 36 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 159 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 18 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 5439 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 4498 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 33 records from Two new species of Petalophthalmus and Ipirophthalmus (Crustacea: Mysida: Petalophthalmidae), from New Zealand. 12 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 3959 records from University of Kentucky Insect Collection. 43510 records from Atlas des Orthoptères et Mantides de France métropolitaine. 23 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 251 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 667 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 14204 records from UAM Bird Collection (Arctos). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 209740 records from uncultured prokaryote Targeted loci environmental. 2 records from Encyocratella olivacea Strand, 1907, a senior synonym of Xenodendrophila gabrieli Gallon, 2003 (Araneae: Theraphosidae: Stromatopelminae) with a description of the male. 303 records from UTEP Herpetology Osteology (Arctos). 2072 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 33889 records from The Scottish Squirrel Database. 96 records from BIRDRACE OAG Neuwerk. 41 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 3 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 74 records from Wood Stork Tracking (aggregated per 1-degree cell). 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 2647 records from SPC CoFish Fish Observations Nauru 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 102 records from A Lichen Survey of the Ben Nevis Plateau. 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 974 records from Survey dataset on Pomatoschistus minutus (Pallas, 1770) and other gobies at the Belgian Coast, Oosterschelde, Westerschelde and at nuclear plants near Doel & Borssele. 1 records from Collection Crustacea - KAUMM. 2146 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 237 records from FBIP: Baboon spider distribution records from selected South African museums. 52 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 315 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 493 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 13 records from Coccolith counts of multinet SO119_MSN1301. 2 records from Données naturalistes de Laurent PONCET. 2242 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 206 records from Review of the braconid parasitoid subfamily Doryctinae (Hymenoptera, Braconidae) from the United Arab Emirates and Yemen. 8 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 21386 records from UWBM Mammalogy Collection (Arctos). 1016 records from Royal Ontario Museum Fungarium (TRTC). 23 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 1266 records from Données d'oiseaux. 82 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 8 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 108 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 5435 records from Mammal records for Dumfries and Galloway. 1 records from Characidium chancoense, a new species of South American darter from the Río Cauca drainage, Colombia (Characiformes: Crenuchidae). 7 records from Moenkhausia rubra, a new species from rio Juruena, upper rio Tapajós basin, Brazil (Characiformes: Characidae). 22 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 103 records from osac_oarisma. 69329 records from Vascular plant herbarium, UiT Tromsø Museum. 189 records from Inventaire des Scléractiniaires de la région du Diahot (RAP). 58 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 521 records from Queens University Belfast Marine Research Data. 1 records from Gryon ancinla Kozlov & Lê (Hymenoptera: Scelionidae): host assocation, expanded distribution, redescription and a new synonymy.. 91 records from BIRDRACE SchrägeVögel. 6635 records from NYSM Mammals. 317 records from iSpot (2008-2010): Shieldbugs & allied species. 6 records from Description, distribution and ecology of endemic Tasmanian quillwort, Isoetes jarmaniae, sp. nov. (Isoetaceae; Lycopodiopsida). 97 records from Streuobstwiese Stedar 2008. 4054 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 576 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 3 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 10754 records from Canadian Museum of Nature Fish Collection. 24566 records from JPB - Herbário Lauro Pires Xavier. 136 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 62 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 16925 records from BioGIS - Mammals - INPA database. 4 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 3 records from A new species of Uvarus Guignot, 1939 (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) from Florida, USA. 1197 records from 2019_MJIM_IN. 2 records from Entomologische Nachrichten und Berichte. 2307 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 9 records from Revision of Netomocera Bouček (Hymenoptera: Chalcidoidea: Pteromalidae), excluding the Oriental species. 2 records from A review of the powderpost beetle genera Xylothrips Lesne, 1901 and Calophagus Lesne, 1902 (Coleoptera: Bostrichidae: Bostrichinae: Xyloperthini). 1 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 8 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 313 records from VIP topsoil data jointsampling soilfauna, 2008. 13 records from An overview of the Brazilian inselberg genus Ameroglossum (Linderniaceae, Lamiales), with the description of seven new species. 149 records from Données du/de la naturaliste CHAPUIS Vincent provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Two new species of Pristimantis (Anura: Craugastoridae) with notes on the distribution of the genus in northeastern Colombia. 26 records from Swedish Malaise Trap Project (SMTP) - Clusiidae. 13701 records from UPCB - Herbário do Departamento de Botânica. 30 records from Taxonomic revision of the South American subgenus Canthon (Peltecanthon) Pereira, 1953 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini). 2151 records from Amphibians and Reptiles census in the Western Siberia (2002 - 2009 years of research). 9 records from A new species of Probolomyrmex from Madagascar.. 373 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE278. 888 records from Database of Eurasian beaver (Castor fiber L., 1758) in Nature Reserves and National Parks of Russia. 1 records from A new species of tree-hole dwelling freshwater crab of the genus Arachnothelphusa Ng, 1991 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from northern Sarawak, Malaysia, Borneo. 16 records from On the huntsman spider genera Sparianthina Banks, 1929 and Anaptomecus Simon, 1903 from South and Central America (Araneae, Sparassidae). 277 records from Phytoplankton abundance at bottle station A1/52. 1023 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 1 records from Lethrus (Lethrus) thracicus (Coleoptera: Geotrupidae), a new species from the European part of Turkey. 2838 records from ZFMK Coleoptera collection. 1 records from Bipolarity in sea slugs: a new species of Doridunculus (Mollusca: Nudibranchia: Onchidoridoidea) from Antarctica. 360 records from Données arachnologiques de LARCHEVEQUE Nelly. 7 records from A review of Peruvian diving beetles of the genus Hydaticus Leach, 1817, with description of Hydaticus (Prodaticus) panguana sp. nov. and notes on other Neotropical species (Coleoptera: Dytiscidae). 6001 records from Records of protected animals species in Ukraine. 223 records from Range table from planktonic foraminifers in ODP Hole 170-1043A. 125 records from annex3. 144 records from Lustbach-Umland. 1 records from Ireland's BioBlitz. 15 records from Benthic macrofauna abundance of sediment core 13200-075. 423 records from Muscidae (Diptera) records from Britain and Ireland to 1985. 336 records from Eschlberg Thalhausen. 45 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 50 records from Larvae collected near deep-sea hydrothermal vent fields for microbiome study. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 163 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 263 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 2303 records from Benthic foraminifers of sediment core Svanic90_9004. 15 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 6 records from A revision of Palaearctic and Oriental Pseudolathra. V. Two new species from Cambodia and Thailand, and additional records (Coleoptera: Staphylinidae: Paederinae). 4 records from Structural variation among species of Leeuwenia (Thysanoptera, Phlaeothripinae) with three new species from Australia. 51 records from Range table from planktonic foraminifers in ODP Hole 173-1067A. 1 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 3 records from Two new enigmatic species of the genus Merodon Meigen (Diptera: Syrphidae) from the north-eastern Middle East. 9 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 21 records from HRC SCC Aerial-Based Monitoring Surveys 2008. 28062 records from Garden Bird Surveys. 331 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 744 records from Données opportunistes. 313 records from Planktic foraminifera counts during POLARSTERN cruise ARK-XIII/2. 647 records from (Table 3) Calcareous nannofossil distribution on ODP Hole 117-720A. 273 records from Freshwater Bullhead Survey Data in Wales. 22 records from Taxonomic studies on the sac spider genus Clubiona (Araneae, Clubionidae) from Xishuangbanna Rainforest, China. 65323 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 149 records from Trockenhang Greinhartsberg Edelfingen. 18 records from Locations at sea of adult females of southern elephant seals (Mirounga leonina) from Península Valdés, Chubut, Argentina. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 10 records from Microplankton abundance in the euphotic zone
Keywords: GBIF; biodiversity; species occurrences